A Randomized Open Label Parallel Group Clinical Study to Evaluate the Efficacy and Safety of Clevira in Fever of Viral Origin - S., Ramesh Kannan; V., Sivraman; Muralikumar, Vanitha R.; M., Sakthibalan; S., Jayashree; Ss, Vanangamudi; Km, Nagarajan; C., Arther Paul (International Journal of Innovative Research in Medical Science, 2019)
Objective: To evaluate the efficacy and safety of Clevira, an ayurvedic formulation in fever of viral origin. Methods: This was a prospective, randomised, multicentre, open label, parallel group interventional clinical end point study. Patients attending general outpatient department, were screened for viral fever including Dengue by using the haematological, Biochemical and microbiological anti body assay for Dengue and NS1 (Non-structural protein) antigen testing. Forty eight patients who satisfied the selection criteria were enrolled in the study. Participants were randomized into 4 groups with 12 patients in each group. Patients were given standard treatment. In addition, Tab. Clevira of Apex laboratories Pvt. Ltd., was administered to test groups. Results: There is highly significant improvement (P<0.001) in the subjects Temperature, fever score, arthralgia score, Myalgia score, Headache and loss of appetite, suggesting a good Analgesic and anti pyretic activity of Clevira. There is a significant improvement in platelet count in the Clevira treated group (P<0.01) when compared to the control group, proving its efficacy in treating thrombocytopenia. The improvement (P<0.01) in the WBC count in the Clevira treated group depicts the anti viral property of Clevira. The overall quality of life was better in Clevira treated group compared to the control group. There were no serious adverse events reported. Conclusion: Clevira is safe and efficacious in reversing thrombocytopenia and thus normalizing the platelet counts and relieving the clinical signs and symptoms (fever, myalgia, arthralgia, headache) of Viral fever associated with thrombocytopenia and other cases of viral fever without thrombocytopenia. Clevira is having good anti-viral, antipyretic, analgesic and immunomodulatory property. Hence, Clevira should be used as an add on drug in patients with viral fever with or without thrombocytopenia for a rapid recovery without any adverse effects.